To Count Our Days : A History of Columbia Theological Seminary - Clarke, Erskine, 1941- (Book collections on Project MUSE., 2019)
"Institutional histories can invite a yawn. They are important for specialists and for those with a personal interest in a specific institution, but as a category of historical writing they do not evoke an imagine of a page-turning narrative. Yet institutions have cultures with their own rituals and character, and they reflect in their own internal life larger historical developments. And institutions, perhaps especially smaller institutions, have within them individual players with their own histories and commitments, quirks and oddities, and those individuals not only help to shape the institution's life but also bring the complexities and mysteries of the human personality to the story of an institution's history. Moreover when an institution exists over many generations, its history is an unfolding story of tension between continuities and change, between remembered ways and practices and the demands of new social and cultural contexts. At least all this has been true for Columbia Theological Seminary"--